Effectiveness of a parent training program on the use of communicative functions in young children with cerebral palsy - Venter, Marissa (My University, 2017)
Background: The relevance and effectiveness of speech therapy interventions for children with Cerebral Palsy (CP) has come under scrutiny within the CP community. There is a need for evidence based research to be conducted within the CP population. Specifically with regard to the current speech therapy interventions that are being used for this population. There is a dearth of literature in favour of the efficacy of speech therapy interventions for the CP population. Furthermore, research within the South African context is required so as to identify the culturally specific needs of the population. In addition, South Africa faces challenges in providing culturally specific, cost effective and evidence based intervention for this population. This can be attributable to barriers such as the lack of human and financial resources. Purpose: The main aim of the study was to measure change in the use of communicative functions of nine children with cerebral palsy following a five week parent training program. The main aim was achieved with the following sub-aims; 1) To assess the participant’s baseline performance in the use of communicative functions before the commencement of the parent training, 2) To assess the participant’s performance in the use of communicative functions after the 5 week parent training had taken place, 3) To assess the participant’s performance in the use of communicative functions 3 months after the post intervention assessment and 4) To describe the effectiveness of a parent training program in improving a child with CP’s ability to make use of communicative functions. Method: The parents of nine children underwent a parent training program namely the Malamulel Onward Carer-2-Carer Training Program. The nine children were assessed before, immediately after and 3 months after the intervention. The scales, namely the Preschool Language Scale-5 and the Communication Matrix were used in the baseline assessment and reassessment phases of the study and yielded numerical data that described the children’s communication abilities. Results: All the children (n=9) demonstrated a positive increase in communication from test 1 through to test 3 on the Communication Matrix. The p-value for test 1 to test 2 was p=0.0078, test 2 to test 3 were p=0.0313 and test 1 to test 2 were p=0.0313 indicating significant change. The performance on the PLS-5 for majority (n=8) of the sample was unexpected. The majority of participants (n=7) displayed an increase in the PLS-5 score from test 1 to test 2; with one participant displaying a positive change across all three testing occasions on the PLS-5. However, a decrease in the PLS-5 score was seen in majority (n=5) of the participants from test 2 to test 3. Conclusion: Based on the findings of this research, the use of parent training appears to be a viable form of intervention to improve the use of communicative functions in children with CP. However, further steps need to be taken to incorporate an individual follow up component after the parent training to ensure carry over and maintenance of skills covered in the workshops. In addition, due to questions around the efficacy of the PLS-5 with individuals who have CP, assessments need to comprise of a standardized tool in addition to an observational tool so as to acquire a more holistic view of a child with CP’s communication skills.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts (Speech Pathology), 2017
Keywords: Cerebral palsied children--Rehabilitation--South Africa; Cerebral palsy--South Africa; Communicative disorders in children--South Africa